176=6n+7(-8-5n)

Simple and best practice solution for 176=6n+7(-8-5n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 176=6n+7(-8-5n) equation:


Simplifying
176 = 6n + 7(-8 + -5n)
176 = 6n + (-8 * 7 + -5n * 7)
176 = 6n + (-56 + -35n)

Reorder the terms:
176 = -56 + 6n + -35n

Combine like terms: 6n + -35n = -29n
176 = -56 + -29n

Solving
176 = -56 + -29n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '29n' to each side of the equation.
176 + 29n = -56 + -29n + 29n

Combine like terms: -29n + 29n = 0
176 + 29n = -56 + 0
176 + 29n = -56

Add '-176' to each side of the equation.
176 + -176 + 29n = -56 + -176

Combine like terms: 176 + -176 = 0
0 + 29n = -56 + -176
29n = -56 + -176

Combine like terms: -56 + -176 = -232
29n = -232

Divide each side by '29'.
n = -8

Simplifying
n = -8

See similar equations:

| n+(-8)= | | X-x^2=-2 | | -4(4m-6)=-104 | | (5x+4y)2= | | 3+6w=-2w | | 7x+9.34=4x+13 | | -87=7+2(-7-5r) | | -48=-3c+9 | | 5x-3y-10=0 | | 12-3(5-1)= | | (-4.93)(-2.1)= | | .6y+1=1.4y-15 | | -126=6(-5+2n) | | 4x^2+26x+12=36 | | y+3=20 | | (39-2x)(21-2x)x=equation | | -5.79+3.11y-4.97-2.13y= | | 0.7x-12=-13.75 | | 10x+5=5(1+2x) | | 16+7r-8+7r=8r+5r | | 3(p-3)+7=32-4(2p+5) | | 4.5(x+7)=41.85 | | 34-6x=6-10x | | 4x+11=-49-6x | | (-8+3i)+(-5i)= | | 2+11x=-48+x | | X+12yi=3-6i | | (2x+1)(3-x)=0 | | 3(4x-1.5)-2x=17 | | 8*(x-2)=32 | | 9+4*x=29 | | 315=7(6m+3) |

Equations solver categories